Implementing Vertical Drainage to Reduce Flood Risk at Settlement Area in Medan - Novrial; Rahman, N. Vinky; Affif, Aulia Malik; Rusmalawaty (Talenta Publisher, 2023)
With the increasing number of residents in a city, there will be excessive exploitation of nature, uncontrolled land use changes and a decrease in the carrying capacity of the environment. These various results have a potential to increase the frequency and severity of flood disasters. Flooding is a problem for the town because it leads in losses of property and lives, the emergence of health issues, damage to different infrastructure facilities and infrastructure, among other things. Although the government has been developing a horizontal drainage system for years, it has yet to decrease urban flooding. Consequently, a new technique is required to overcome flooding, specifically the use of vertical drainage. In an attempt to improve the community's living conditions, this activity's goal is to reduce the risk of flooding in Kelurahan Pasar Merah Timur settlement area. The advantages of this program include an improvement in the community's quality of life as a result of less intense flooding following the installation of vertical drainage. According to the test, 2 liters of water can be drained into the aquifer channel every second by the vertical drainage. So it can be assumed that if there is a puddle of water that cannot be drained by horizontal drainage of 4000 liters or 4 m3, it will take 34 minutes to deliver the water into the aquifer layer.